Function matters: Coronavirus cross-binding antibodies do not cross-neutralize - Farcet, Maria R.; Schwaiger, Julia; Karbiener, Michael; Kreil, Thomas R. (Frontiers in Medicine, 2022)
Background During the current pandemic, the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) neutralization capacity of the immunoglobulin (IG) supply has changed from undetectable for lots manufactured from plasma collected before the pandemic, to now highly potent. Objective As antibodies induced by exposure to or vaccination against coronaviruses were shown to be cross-coronavirus reactive, it was of interest to understand whether SARS-CoV-2 neutralizing antibodies would result in increased functional IG potency also against seasonal coronaviruses. Methods IG lots from US plasma collected before SARS-CoV-2 emerged and collected during the pandemic were analyzed by live virus neutralization assay for SARS-CoV-2 and seasonal human coronaviruses (HCoVs) NL63 and OC43 neutralizing antibody content. Results Pre-pandemic IG showed no SARS-CoV-2 neutralizing antibody titers. However, IG lots produced from plasma of post-coronavirus disease 2019 (COVID-19) individuals exhibited robust anti-SARS-CoV-2 potency (1,267 IU/ml) which further increased ~4-fold in pandemic IG lots reaching a mean titer of 5,122 IU/ml. Nonetheless, neutralizing antibody potencies to the HCoVs NL63 and OC43 remained stable over this period, i.e., have not increased correspondingly. Conclusion The present results show that cross-coronavirus-reactive antibodies are not cross-neutralizing, i.e., SARS-CoV-2 antibodies do not neutralize seasonal coronaviruses NL63 and OC43.